Assessment Online Learning At Elementary School - Zaitun Zaitun; Rochmiyati Rochmiyati; Pargito Pargito (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the assessment model for online-based elementary school teachers during the Covid-19 pandemic. This research was carried out at SDN 2, Palas District, South Lampung Regency. The research method used in this study is a qualitative research method with a descriptive study approach. The data collection techniques used are through questionnaires and interviews. The results showed that the online assessment in elementary schools during the Covid-19 pandemic was carried out through: assignments, daily exercises (oral tests), written tests and portfolios. From the various types of assessments carried out, it turns out that there are several obstacles, from the results of interviews that have been conducted, the obstacles experienced in online assessments are skills and attitude assessments to overcome the obstacles regarding online assessment, it still needs to be developed again, namely self-assessment and parental assessment to help solve problems regarding attitude and skill assessment.